Effective rates of protection in Brazil: From 2000 to 2015 - Carolina Bloch; Sergei Soares (Institute for Applied Economic Research (ipea), 2019)
This paper calculates effective tariffs by economic sector for Brazil from 2000 to 2015. The effective tariff differs from the nominal tariff in that it takes into consideration the protection given to inputs along the production chain. A sector whose products are protected by high tariffs may also be burdened by high tariffs on its inputs, leading to a lower effective tariff. Two series are calculated: 2000 to 2009 and 2010 to 2015. The reason for this is that the National Accounts changed their classification of economic sectors in 2010. Results indicate that: i) effective rates of protection are highly varied in Brazil, according to sector; ii) effective rates of protection have become slightly more homogeneous in the 15 years from 2000 to 2015; and iii) some sectors have seen their rates of protection vary considerably over this fifteen-year period, but most did not.
Keywords: 330; trade policy; effective rates of protection; nominal rates of protection